Identifier les facteurs clés d’un système d’indicateurs de développement durable : l’expérience du projet DURAMAZ sur l’Amazonie brésilienne - Guillaume Marchand (Unité Mixte de Recherche 8504 Géographie-cités, 2012)
Created in a multidisciplinary research program, the IDURAMAZ system of indicators focuses on the territorial impacts of different projects of sustainable development implemented in Amazonian rural areas during the last twenty years. Originally constructed to be subdivided in 4 synthetic indexes, 14 indicators and 44 sub-indicators related to socioeconomic, environmental, institutional and generational questions, we wanted to reduce the number of its components and its architecture in order to obtain a dashboard of more relevant indicators. During the realization of the key indicators selection, we focused on two main goals. First, making our methodology more intelligible to the targeted public by conserving the most explicit indicators and limiting the use of composed ones (those that are constructed with different variables). Second, facilitating the research on the determinants of sustainability, which means the most important criteria for the success or the failure of the projects realized in its name. This paper exposes the principles that have piloted the selection of the key indicators, the results obtained as to the key factors of sustainability and some reflections about the themes to be added. Behind the reflections on the DURAMAZ project and its indicators system, this paper has a more general range on the way to select a core set of indicators to approach the question of sustainability.